MOCVD growth of thick V-pit-free InGaN films on semi-relaxed InGaN substrates. (17th November 2020) - White, Ryan C; Khoury, Michel; Wu, Feng; Keller, Stacia; Rozhavskaia, Mariia; Sotta, David; Nakamura, Shuji; DenBaars, Steven P
Abstract: The MOCVD growth of InGaN:Si base layers on a semi-relaxed InGaN substrate, where growth is generally difficult due to the presence of V-pits, is examined. These V-pits can propagate through the crystal, causing severe morphological degradation and significantly reducing material quality for device use. Such V-pits may also be a source of leakage current if they extend from the substrate through p-n junction. A wide range of InGaN growth conditions and their impact on V-pit formation and density are investigated. The use of thin GaN interlayers, carrier gas selection, and V/III ratio are found play a critical role in managing V-pit quantity and size. Finally, high temperature GaN interlayers are implemented, fully eliminating V-pit formation in 1200 nm thick InGaN base layers grown coherently on semi-relaxed InGaN substrates.